DEVELOPMENT OF AN INTEGRATIVE MODEL OF MULTICULTURAL EDUCATION VALUES IN LEARNING FOR STUDENTS STKIP MUHAMMADIYAH MANOKWARI - Gunawan Gunawan; Syamsul Bachri Thalib; Darman Manda (Adisam Publisher, 2025)
This research aims to: 1) obtain an overview of the needs of multicultural education-based learning models; 2) obtain comprehensive information in designing multicultural education-based learning models for students; 3) produce valid multicultural education-based learning models based on the assessment of validators; 4) produce practical multicultural education-based models; and 5) produce effective multicultural education-based learning models. This research is a research and development by adopting Borg and Gall design. The research subjects involved consisted of: (1) 30 STKIP Muhammadiyah Manokwari students, (2) two experts from Makassar State University, and (3) two Indonesian lecturers. Data collection was carried out with several instruments in the form of needs analysis questionnaires, interviews, validation questionnaires, observation sheets, lecturer response questionnaires, student response questionnaires, and observations. The data were then analyzed using qualitative and quantitative methods. The results showed that there was a need for the development of an integrative model of multicultural education value. The validation test results showed that the model book and learning tools were declared valid based on the experts' assessment. Furthermore, the results of the practicality test also stated that this model proved to be practical based on the results of observations of learning implementation, lecturer response questionnaires, and student response questionnaires. Finally, the results of the effectiveness test through the measurement of the N-Gain test from the performance test data and student observation results show that this multicultural education value integrative model is declared effective for increasing students' multicultural understanding